Association between occupational stress and mental health in an automobile manufacturing factory in Iran - Eftekhari, Sahar; Karimi, Leila; Sharifian, Seyed Akbar; Aminian, Omid; Rasooli, Seyed Ramin; Zia, Ghasem (International Journal of Occupational Safety and Health, 2025)
Introduction: This study aimed to assess the relationship between occupational stress and the symptoms of anxiety, depression, and stress among the employees of an automobile manufacturing factory in Iran.Methods: This was a cross-sectional analytical study of employees in the automobile manufacturing industry. OSIPOW occupational stress and Depression Anxiety and Stress Scale 21 (DASS-21) questionnaires were used to collect data.Results: In our survey, 4565 employees with a mean age of 42.59 ± 4.45 years were evaluated. All the participants had some degree of job stress, 33.3% were in low-stress group and 66.7% were in high-stress group. White collar workers had higher job stress compared to blue collar workers. The prevalence of the symptoms of depression, anxiety, and stress symptoms was 22.6%, 24%, and 29.3%, respectively. The participants with high job stress reported higher symptoms of depression, anxiety, and stress [OR=3.40, CI 95% (2.83-4.10)], [OR=2.35, CI 95% (1.99-2.78)], [OR=2.26, CI 95% (1.94-2.63)]. In linear regression analysis, being white collar, having higher work experience, exposure to noise and stressors in the workplace, and having symptoms of depression are recognized as the factors that might be involved in creating occupational stress.Conclusion: This research provides further support regarding the negative effects of the psychosocial hazards of the work environment on the mental health of the workers which was evaluated by measuring depression, anxiety, and stress symptoms. There is a need to manage employee’s occupational stress to maintain the general health of human resources, as well as mental health.